Design of an Interactive Dashboard For Performance Monitoring of The Management Development at PT Kalimantan Prima Persada - Siahaan, Jeferson; Situmorang, Relay Basando (CV ODIS, 2025)
PT Kalimantan Prima Persada is an integrated mining contractor services company operating in the coal, gold, and nickel sectors. This research is driven by issues in the reporting and monitoring process of performance achievements for the Management Development position within the Corporate Planning Management Development Department, including delays in reporting, incomplete performance achievement data and documentation, and the absence of an integrated platform to collect, manage, and present performance achievement information across all mining districts on a monthly basis. To address these challenges, this study aims to design an integrated platform using the User-Centered Design (UCD) method to systematically collect, manage, and present performance achievement information. The outcome of this research is a dashboard that includes the Main Dashboard, Strategic Management Index, Evidence Strategic Management Index, Strategic Management Effectiveness, Evidence Strategic Management Effectiveness, Follow-Up ASAP, System Management, Evidence System Management, EIIC (Employee Innovation Involvement Cover), CI Infrastructure, and CI Performance. Testing results show that the developed dashboard functions effectively and meets user requirements. It is expected that this dashboard will enhance the effectiveness and efficiency of performance monitoring and evaluation processes